Exploring decadal beach profile dynamics in response to nourishment strategies under accelerated sea level rise - Tosca Kettler; Matthieu de Schipper; Arjen Luijendijk (Ocean & Coastal Management, 2025)

Simulating decadal cross-shore dynamics at nourished coasts with Crocodile - Tosca Kettler; Matthieu de Schipper; Arjen Luijendijk (Coastal Engineering, 2024)

Predicting marine and aeolian contributions to the Sand Engine’s evolution using coupled modelling - Bart van Westen; Arjen P. Luijendijk; Sierd de Vries; Nicholas Cohn; Tim W.B. Leijnse; Matthieu A. de Schipper (Coastal Engineering, 2024)

Wave-Current Impact on Shear Stress Patterns around 3D Shallow Bedforms - Julia Hopkins; Matthieu de Schipper; Meagan Wengrove; Bruno Castelle (Journal of Marine Science and Engineering, 2022)
Observations from wave basin experiments and wave-resolving numerical simulations demonstrate the effect of wave-current interaction on shear stress around a sandy mound. Observations from the wave basin show that the mound deformation rate and morphological patterns depend on the mixture of waves and currents in the incident flow conditions. A SWASH nonhydrostatic numerical model was used to expand the parameter space of wave-current conditions observed in the flume and characterize the response of the near-bed shear stress to the mound. The model was validated with observations from wave-alone, current-alone, and wave-current flume tests and then ran for a suite of numerical flow conditions which isolate the impact of the ratio of wave-current energy on the bed shear stress. Results show how the current-to-wave ratio impacts the spatial heterogeneity of shear stress across the mound, with the region of shear stress intensification around the mound and the location of the peak shear stress becoming asymmetric with more mixed wave-current flows. These results show the nonlinear response of shear stress patterns to combined wave-current flows and how these patterns may impact eventual sediment transport and mound evolution.

Subaqueous and Subaerial Beach Changes after Implementation of a Mega Nourishment in Front of a Sea Dike - Anna Kroon; Matthieu de Schipper; Sierd de Vries; Stefan Aarninkhof (Journal of Marine Science and Engineering, 2022)
Sandy nourishments can provide additional sediment to the coastal system to maintain its recreational or safety function under rising sea levels. These nourishments can be implemented at sandy beach systems, but can also be used to reinforce gray coastal infrastructure (e.g., dams, dikes, seawalls). The Hondsbossche Dunes project is a combined shoreface, beach, and dune nourishment of 35 million m3 sand. The nourishment was built to replace the flood protection function of an old sea-dike while creating additional space for nature and recreation. This paper presents the evolution of this newly created sandy beach system in the first 5 years after implementation based on bathymetric and topographic surveys, acquired every three to six months. A significant coastline curvature is created by the nourishment leading to erosion in the central 7 km bordered by zones with accretion. However, over the five-year period, net volume losses from the project area were less than 5% of the initial nourished sand volume. The man-made cross-shore beach profile rapidly mimics the characteristics of adjacent beaches. The slope of the surfzone is adjusted within two winters to a similar slope. The initially wide beaches (i.e., up to 225 m) are reduced to about 100 m-wide. Simultaneously, the dune volume has increased and the dune foot migrated seaward at the entire nourished site, regardless of whether the subaqueous profile gained or lost sediment. Our results show that the Hondsbossche Dunes nourishment, built with a natural slope and wide beach, created a positive sediment balance in the dune for a prolonged period after placement. As such, natural forces in the years after implementation provided a significant contribution to the growth in dune volume and related safety against flooding.

North Sea Infragravity Wave Observations - Ad J.H.M. Reniers; Remy Naporowski; Marion F. S. Tissier; Matthieu A. de Schipper; Gal Akrish; Dirk P. Rijnsdorp (Journal of Marine Science and Engineering, 2021)
Coastal safety assessments with wave-resolving storm impact models require a proper offshore description for the incoming infragravity (IG) waves. This boundary condition is generally obtained by assuming a local equilibrium between the directionally-spread incident sea-swell wave forcing and the bound IG waves. The contribution of the free incident IG waves is thus ignored. Here, in-situ observations of IG waves with wave periods between 100 s and 200 s at three measurement stations in the North Sea in water depths of O(30) m are analyzed to explore the potential contribution of the free and bound IG waves to the total IG wave height for the period from 2010 to 2018. The bound IG wave height is computed with the equilibrium theory of Hasselmann using the measured frequency-directional sea-swell spectra as input. The largest IG waves are observed in the open sea with a maximum significant IG wave height of O(0.3) m at 32 m water depth during storm Xaver (December 2013) with a concurrent significant sea-swell wave height in excess of 9 m. Along the northern part of the Dutch coast, this maximum has reduced to O(0.2) m at a water depth of 28 m with a significant sea-swell wave height of 7 m and to O(0.1) m at the most southern location at a water depth of 34 m with a significant sea-swell wave height of 5 m. These appreciable IG wave heights in O(30) m water depth represent a lower bound for the expected maximum IG wave heights given the fact that in the present analysis only a fraction of the full IG frequency range is considered. Comparisons with the predicted bound IG waves show that these can contribute substantially to the observed total IG wave height during storm conditions. The ratio between the predicted bound- and observed total IG variance ranges from 10% to 100% depending on the location of the observations and the timing during the storm. The ratio is typically high at the peak of the storm and is lower at both the onset and waning of the storm. There is significant spatial variability in this ratio between the stations. It is shown that differences in the directional spreading can play a significant role in this. Furthermore, the observed variability along the Dutch coast, with a substantially decreased contribution of the bound IG waves in the south compared to the northern part of the Dutch coast, are shown to be partly related to changes in the mean sea-swell wave period. For the southern part of the Dutch coast this corresponds to an increased difference with the typically assumed equilibrium boundary condition although it is not clear how much of the free IG-energy is onshore directed barring more sophisticated observations and/or modeling.

Observed Changes of a Mega Feeder Nourishment in a Coastal Cell: Five Years of Sand Engine Morphodynamics - Bart Roest; Sierd de Vries; Matthieu de Schipper; Stefan Aarninkhof (Journal of Marine Science and Engineering, 2021)
Recently, mega feeder nourishments have been proposed as a new strategy to nourish sediment-starving beaches. This strategy involves the placement of a large, concentrated sediment volume at a single location along the coast. Wind, waves and currents act as the natural agents to spread the sediment alongshore over the course of years to decades. This article presents the morphological development of the first full-scale implementation of this strategy, examining the 20 × 106 m3“Sand Engine” feeder nourishment and its impact on adjacent coastal sections. The analysis is based on 37 high-resolution topographical surveys, executed in a 17 km coastal cell. These unique data describe the alongshore spreading in the first five years and the response at different elevations of the coastal profile. The analysis shows rapid transformation of the nourishment’s planform shape, changing rapidly into a smooth (Gaussian-like) shape which is gradually extending alongshore over time. Within five years, sediment has been distributed to a 5.8 km stretch of coast from the initial 2.2 km peninsula footprint. Changes in cross-shore and alongshore extent varied strongly over depth, with the strongest morphological response at the mean sea level (MSL) isobath and limited morphodynamic activity at deeper water, below −8 m MSL. This depth-dependent response has resulted in decreasing subtidal slopes in eroding areas, accretive areas contrastingly show a slope increment. These results yield important insights in nourished sediment mobility at different depths near the coast and distribution over a larger coastal cell. However, this single-design assessment cannot address the wide range of mega nourishment design parameters essential for morphological development of its coastal cell. This work suggests limiting cross-shore extent, since it is uncertain whether nourished sediment at deeper water will become active in the coastal system. A continuation of the current monitoring and future research might shed more light on this.

Morphodynamic Acceleration Techniques for Multi-Timescale Predictions of Complex Sandy Interventions - Arjen P. Luijendijk; Matthieu A. de Schipper; Roshanka Ranasinghe (Journal of Marine Science and Engineering, 2019)
Thirty one percent (31%) of the world’s coastline consists of sandy beaches and dunes that form a natural defense protecting the hinterland from flooding. A common measure to mitigate erosion along sandy beaches is the implementation of sand nourishments. The design and acceptance of such a mitigating measure require information on the expected evolution at time scales from storms to decades. Process-based morphodynamic models are increasingly applied, together with morphodynamic acceleration techniques, to obtain detailed information on this wide scale of ranges. This study shows that techniques for the acceleration of the morphological evolution can have a significant impact on the simulated evolution and dispersion of sandy interventions. A calibrated Delft3D model of the Sand Engine mega-nourishment is applied to compare different acceleration techniques, focusing on accuracy and computational times. Results show that acceleration techniques using representative (schematized) wave conditions are not capable of accurately reproducing the morphological response in the first two years. The best reproduction of the morphological behavior of the first five years is obtained by the brute force simulations. Applying input filtering and a compression factor provides similar accuracy yet with a factor five gain in computational cost. An attractive method for the medium to long time scales, which further reduces computational costs, is a method that uses representative wave conditions based on gross longshore transports, while showing similar results as the benchmark simulation. Erosional behavior is captured well in all considered techniques with variations in volumes of about 1 million m 3 after three decades. The spatio-temporal variability of the predicted alongshore and cross-shore distribution of the morphological evolution however have a strong dependency on the selected acceleration technique. A new technique, called ’brute force merged’, which incorporates the full variability of the wave climate, provides the optimal combination of phenomenological accuracy and computational efficiency (a factor of 20 faster than the benchmark brute force technique) at both the short and medium to long time scales. This approach, which combines realistic time series and the mormerge technique, provides an attractive and flexible method to efficiently predict the evolution of complex sandy interventions at time scales from hours to decades.

Observations and Modelling of Shoreface Nourishment Behaviour - Bastiaan Huisman; Dirk-Jan Walstra; Max Radermacher; Matthieu de Schipper; B. Gerben Ruessink (Journal of Marine Science and Engineering, 2019)
Shoreface nourishments are commonly applied for coastal maintenance, but their behaviour is not well understood. Bathymetric data of 19 shoreface nourishments located at alongshore uniform sections of the Dutch coast were therefore analyzed and used to validate an efficient method for predicting the erosion of shoreface nourishments. Data shows that considerable cross-shore profile change takes place at a shoreface nourishment, while an impact at the adjacent coast is hard to distinguish. The considered shoreface nourishments provide a long-term (3 to ∼30 years) cross-shore supply of sediment to the beach, but with small impact on the local shoreline shape. An efficient modelling approach is presented using a lookup table filled with computed initial erosion–sedimentation rates for a range of potential environmental conditions at a single post-construction bathymetry. Cross-shore transport contributed the majority of the losses from the initial nourishment region. This transport was driven partly by water-level setup driven currents (e.g., rip currents) and increased velocity asymmetry of the waves due to the geometrical change at the shoreface nourishment. Most erosion of the nourishment takes place during energetic wave conditions ( H m 0 ≥ 3 m) as milder waves are propagated over the nourishment without breaking. A data-model comparison shows that this approach can be used to accurately assess the erosion rates of shoreface nourishments in the first years after construction.